Formaldehyde and acetaldehyde emissions from residential wood combustion in Portugal - Cerqueira, Mário; Gomes, Luís; Tarelho, Luís; Pio, Casimiro (Atmospheric Environment, 2013)
A series of experiments were conducted to characterize formaldehyde and acetaldehyde emissions from residential combustion of common wood species growing in Portugal. Five types of wood were investigated: maritime pine (Pinus pinaster), eucalyptus (Eucalyptus globulus), cork oak (Quercus suber), holm oak (Quercus rotundifolia) and pyrenean oak (Quercus pyrenaica). Laboratory experiments were performed with a typical wood stove used for domestic heating in Portugal and operating under realistic home conditions. Aldehydes were sampled from diluted combustion flue gas using silica cartridges coated with 2,4-dinitrophenylhydrazine and analyzed by high performance liquid chromatography with diode array detection. The average formaldehyde to acetaldehyde concentration ratio (molar basis) in the stove flue gas was in the range of 2.1–2.9. Among the tested wood types, pyrenean oak produced the highest emissions for both formaldehyde and acetaldehyde: 1772 ± 649 and 1110 ± 454 mg kg−1 biomass burned (dry basis), respectively. By contrast, maritime pine produced the lowest emissions: 653 ± 151 and 371 ± 162 mg kg−1 biomass (dry basis) burned, respectively. Aldehydes were sampled separately during distinct periods of the holm oak wood combustion cycles. Significant variations in the flue gas concentrations were found, with higher values measured during the devolatilization stage than in the flaming and smoldering stages.
Keywords: Acetaldehyde; Biomass combustion; Emissions; Formaldehyde; Wood stove

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Exchange of short-chain oxygenated volatile organic compounds (VOCs) between plants and the atmosphere: A compilation of field and laboratory studies - Kesselmeier, J (Journal of Atmospheric Chemistry, 2001)
Field and laboratory investigations of the exchange of the short-chain organic acids – formic acid and acetic acid – as well as their homologous aldehydes are discussed. Both acids are substantially released from several plant species. Emission measurements under ﬁeld conditions are compiled to give an overview of three years of measurements. Emission rates from several tree species were found in the range between zero and 60 nmoles m−2 min−1 for acetic acid and between zero and 90 nmoles m−2 min−1 for formic acid though also a deposition has been observed to orange trees. Investigations under laboratory conditions showed an order of magnitude lower emission rates with signiﬁcant differences under light and dark conditions, and a deposition was observed under certain conditions. Hence, low emission rates or even a bi-directional exchange, emission as well as deposition have to be taken into account. Further differences between ﬁeld and laboratory studies are discussed considering age of trees, stress effects and a potential production of acids by photochemical conversion of precursors inside enclosures during sampling. Field data on the exchange of formand acetaldehyde show a complex behavior. We found emission as well as uptake. The bi-directional exchange is signiﬁcantly triggered by the ambient mixing ratios of both aldehyde species and exhibits a compensation point. Further studies are needed for generalization of the exchange of these and potentially also for other compounds
Keywords: Acetaldehyde; acetic acid; biogenic deposition; Biogenic emission; carbonyls; compensation point; Formaldehyde; formic acid; organic acids; Volatile Organic Compounds